2021
DOI: 10.5980/jpnjurol.112.159
|View full text |Cite
|
Sign up to set email alerts
|

EFFICACY AND SAFETY OF 25 AND 50 μg DESMOPRESSIN ORALLY DISINTEGRATING TABLETS IN NOCTURIA DUE TO NOCTURNAL POLYURIA IN JAPANESE MALE PATIENTS

Abstract: Purpose) To conduct a prospective study on the efficacy and safety of desmopressin for nocturnal polyuria.(Materials and methods) We selected 51 Japanese men, aged !50 years, with complaints of nocturia and a nocturnal polyuria index of !0.33. We administered 25 or 50 μg desmopressin (Minirinmelt Orally Disintegrating Tablet Ⓡ ), once daily at bedtime. We evaluated the nighttime urinary frequency and urine volume, nocturnal polyuria index, time to the first urination after falling asleep, and International Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…7 Additionally, Hayashi et al found that HUS was significantly extended in the 50 μg group, but not significantly extended in the 25 μg group. 9 The report by Kyoda et al found no significant difference in the onset of hyponatremia between the initial doses of 50 or 25 μg. 7 Based on the results of these studies, the initial dose of desmopressin was set as 50 μg in this study.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…7 Additionally, Hayashi et al found that HUS was significantly extended in the 50 μg group, but not significantly extended in the 25 μg group. 9 The report by Kyoda et al found no significant difference in the onset of hyponatremia between the initial doses of 50 or 25 μg. 7 Based on the results of these studies, the initial dose of desmopressin was set as 50 μg in this study.…”
Section: Discussionmentioning
confidence: 92%
“…A study by Kyoda et al on clinical practice in Japanese patients reported that the frequency of night‐time urination reduced 1.3 times compared with the baseline in the desmopressin 25 μg group, and 1.8 times in the 50 μg group with 1 to 3 months of treatment, demonstrating a dose‐dependent therapeutic effect 7 . Additionally, Hayashi et al found that HUS was significantly extended in the 50 μg group, but not significantly extended in the 25 μg group 9 . The report by Kyoda et al found no significant difference in the onset of hyponatremia between the initial doses of 50 or 25 μg 7 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Desmopressin was approved in Japan in 2019 for the treatment of nocturia associated with nocturnal polyuria in men, and evidence regarding its safety and efficacy is currently being accumulated. However, reports regarding effect predictors of desmopressin are scarce (8,12). Nocturia is known to affect sleep; in particular, a nocturnal voiding frequency >2 reduces sleep quality and total sleep time, and decreases sleep quality and QOL (13).…”
Section: Discussionmentioning
confidence: 99%